RESTORATIVE JUSTICE POLICY IN HANDLING TRAFFIC ACCIDENT CASES IN THE JURISDICTION OF WONOSOBO POLICE - Nurhasan, M. Nurhasan (UNISSULA Semarang, 2023)
The Restorative Justice Policy in Wonosobo District Police is conducted to create a sense of justice and humanity, prioritizing the interests of victims and perpetrators to reach an agreement together to seek a solution to the crime and its implications by emphasizing on recovery rather than retaliation.The method used is sociological juridical research. Specification of research that writer use that is descriptive qualitative. Data collection techniques with interviews to the parties involved in research, direct observation and document recording.Factors that hamper the investigator unit laka then Polres Wonosobo in the implementation of restorative justice that there are families of victims who do not want to forgive the perpetrators because the losses suffered by the victim is large enough that the victim's family demanded a substantial amount of compensation where the family of perpetrators who came from ordinary family Find it difficult to meet the demands of the victim's family and there is still a negative stigma of the community, especially the victims against law enforcement officers in applying the concept of restorative justice.Keword :Restorative Justice, Criminal Act, Traffic accident.